The patrimonial lability of the State and the protection to the public patrimony in Colombia. The culture of anticipation as a central and articulating element of an urgent, necessary and possible conciliation - Peláez Gutierrez, Juan Carlos (Universidad Nacional del Litoral, 2021)
Faced with the question of how the problem arising from the patrimonial liability of the State and the protection to the public patrimony as conflicting extremes should be addressed legally, in the framework of the Public Legal Defense in Colombia, our response is strong. The legal way to address the problem arising from the patrimonial liability of the State and the protection to the public patrimony as conflict extremes, within the framework of the Public Legal Defense in Colombia, is from the perspective of the Culture of Anticipation as a central and articulating element of an urgent, necessary and possible conciliation.